Banks as shadow directors - O’Donovan, James (Victoria University of Wellington Law Review, 1995)
In some circumstances, the bank may be classified as a de facto director with attendant legal obligations. This article discusses the role of banks in "intensive care assignments". The article begins with the problem areas in the law found in provisions of the Companies Act 1955 and 1993, as well as in cases like Re Tasbian (No 3) [1991] BCC 436. The article provides possible solutions to the problems, including the bank ensuring that the company engages the external consultant and that the consultant is not directed or instructed by the bank, or for the bank to appoint a receiver and manager under its mortgage or mortgage debenture. The author concludes that the new companies law regime, like a traditional receivership, avoids all the problems of a de facto directorships and shadow directorships.